Hybrid Network Mobility Support in Named Data Networking - Zhiwei Yan; Yong-Jin Park; Yu-Beng Leau; Lee Ren-Ting; Rosilah Hassan (2020)
Named Data Networking (NDN) is a promising Internet architecture which is expected to solve some problems (e.g., security, mobility) of the current TCP/IP architecture. The basic concept of NDN is to use named data for routing instead of using location addresses like IP address. NDN natively supports consumer mobility, but producer mobility is still a challenge and there have been quite a few research. Considering the Internet connection such as public transport vehicles, network mobility support in NDN is important, but it is still a challenge. That is the reason that this paper proposes an efficient network mobility support scheme in NDN in terms of signaling protocols and data retrieval.